If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(2x-4)-x=8-3x
We move all terms to the left:
2(2x-4)-x-(8-3x)=0
We add all the numbers together, and all the variables
2(2x-4)-x-(-3x+8)=0
We add all the numbers together, and all the variables
-1x+2(2x-4)-(-3x+8)=0
We multiply parentheses
-1x+4x-(-3x+8)-8=0
We get rid of parentheses
-1x+4x+3x-8-8=0
We add all the numbers together, and all the variables
6x-16=0
We move all terms containing x to the left, all other terms to the right
6x=16
x=16/6
x=2+2/3
| 1/3*(x-5)+2x=16 | | 2x=44-9x | | 1/3(x-5)+2x=16 | | 27=12+x=11 | | -2x^2-9x+12=0 | | X÷5-3=x÷10+4 | | -(4x-1)=-2x+4 | | 3×-8y=-16 | | 4x+15x=3500 | | 3^(x+1)*2^x=5^(2x) | | 93-36t=82 | | 2m-13=9 | | 3y+11=35 | | 3×+2y=22 | | 325=0.65x | | -41+3x=-23-8 | | 7x^2-20x-3/(x^2+1)=0 | | (2x+7)=5x+3 | | 46x+56=0 | | 46x-56=0 | | 2^x*4^(x+1)=70 | | 3h/4-10=18 | | h+h*0,07*5/12=35000 | | p/100*1300=700 | | 60/x=83/100 | | 15x^2-8-14x=0 | | x+10+x+x+10+10=180 | | 4p+2=1 | | -3/4x+3=9 | | 2x-70=110 | | 7/3x+5=17/2 | | 3(m–2)–5=25 |